KINERJA UNIT PELAKSANA TEKNIS (UPT) MUSEUM DAERAH DAN TAMAN BUDAYA PROVINSI RIAU - Arrauda Dhiza; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This This research is based on the phenomenon of the number of tupoksi from TIU Regional Museum and Cultural Park which is not running optimally. Because the performance generated by UPT Regional Museum and Cultural Park has an important role for the progress of the Regional Museum activity of Sang Nila Utama because it is a determining factor of walking or not the activity of the museum it self.This research aims to determine the performance of Technical Implementation Unit (TIU) Regional Museum and Cultural Park Riau Province, as well as to determine the factors that influence it. The theoretical concept used is Agus Dwiyanto's theory which is indicator in public organization performance appraisal, productivity, service quality, responsiveness, responsibilitas, and accountability. The type of research used is descriptive qualitative. Data collection techniques are done through observation, interviews, and documentation and all information is collected, analyzed, and studied in order to become a unified whole.The results showed that the productivity of TIU Museum Regional and Cultural Park of Riau Province has not been fully optimal, The quality of service provided by TIU Regional Museum and Cultural Park in this case the performance of educational guidance staff is inconsistent, Responsiveness Museum of Regional and Cultural Park of Riau Province can not be said Both as a public organization, the Responsiblity owned by Regional Museum and Crocodile Garden is still low, TIU Regional Museum Accountability and Taman Budaya Riau Province is still not optimal. Factors affecting the performance of Technical Implementation Unit (TIU) Regional Museum and Cultural Park are the inadequacy of facilities and infrastructure that can support the performance of Regional Museum and Cultural Park, and the lack of quality and quantity of human resources (HR) contained within the UPT Museum Regional and Cultural Park.Keywords: Performance, Organitatition